2011
DOI: 10.1074/jbc.m110.210245
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein L6, Induced in Atherosclerotic Lesions, Promotes Apoptosis and Blocks Beclin 1-dependent Autophagy in Atherosclerotic Cells

Abstract: Inflammatory cytokine-regulated apoptosis and autophagy play pivotal roles in plaque rupture and thrombosis of atherosclerotic lesions. However, the molecular interplay between apoptosis and autophagy in vascular cells has not been investigated. Our prior study showed that human apolipoprotein L6 (ApoL6), a pro-apoptotic BH3-only member of the Bcl-2 family, was one of the downstream targets of interferon-␥ (INF␥), which sensitizes atherosclerotic lesion-derived cells (LDCs) to Fas-induced apoptosis. To investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 56 publications
3
65
0
Order By: Relevance
“…APOL1, 3 and 6 were also downregulated with miR-187 overexpression. APOL1 and APOL6 proteins have been identified as regulators of autophagy (40,41). OAS1 encodes a protein of the 2′-5′ OAS family, which is involved in the innate immune response, the OAS2 and OASL genes were also downregulated with miR-187 overexpression.…”
Section: Resultsmentioning
confidence: 99%
“…APOL1, 3 and 6 were also downregulated with miR-187 overexpression. APOL1 and APOL6 proteins have been identified as regulators of autophagy (40,41). OAS1 encodes a protein of the 2′-5′ OAS family, which is involved in the innate immune response, the OAS2 and OASL genes were also downregulated with miR-187 overexpression.…”
Section: Resultsmentioning
confidence: 99%
“…Other members of the ApoL family are predicted to lack a signal peptide, and it is unclear whether they are secreted. Human ApoL6 was reported to promote apoptosis and to inhibit autophagy (46,47), both of which might affect viral replication. In a broad ISG screen for antiviral activity, Schoggins et al (39) observed an antiviral activity for several members of the human ApoL family.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, extracellular pathogens are thought to have shaped the evolution of APOL1, whereas intracellular pathogens would have driven evolution of the other APOL genes [7]. The up-regulation of APOL genes by pro-inflammatory cytokines (e.g., interferon-γ [IFNγ] and tumor necrosis factor [TNF]) and their involvement in autophagy and apoptosis suggest that most APOL genes may be involved in innate immune defense[10,12,13,15]. …”
Section: The Evolution Of Apol Family Genesmentioning
confidence: 99%
“…Multiple mechanisms have been proposed for how APOL1 might contribute to glomerulopathies, including lysosomal membrane permeabilization [24,25], autophagic cell death [10,12,26], apoptosis [7,11], and necrosis [24], but clearly much emphasis has been placed on cell death. Non-risk APOL1 (G0) induces autophagic cell death in p53-null human colorectal cancer cells [10], but this pathway of programmed cell death is not well understood and remains controversial [2729].…”
Section: Possible Pathomechanisms: Apol1 Toxicitymentioning
confidence: 99%